Suppose that the functions \( q \) and \( r \) are defined as follows, \( \begin{array}{l}q(x)=-4 x+5 \\ r(x)=x+3 \\ \text { Find the following. } \\ (r \circ q)(2)=\square \\ (q \circ r)(2)=\square\end{array} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To solve for \( (r \circ q)(2) \) and \( (q \circ r)(2) \), we first need to understand what these compositions mean. 1. **Calculating \( (r \circ q)(2) \)**: This means we first apply \( q \) to \( 2 \), and then apply \( r \) to the result. \[ q(2) = -4(2) + 5 = -8 + 5 = -3 \] Now, apply \( r \) to \( -3 \): \[ r(-3) = -3 + 3 = 0 \] So, \( (r \circ q)(2) = 0 \). 2. **Calculating \( (q \circ r)(2) \)**: Here, we apply \( r \) to \( 2 \) first, and then apply \( q \) to that result. \[ r(2) = 2 + 3 = 5 \] Now, apply \( q \) to \( 5 \): \[ q(5) = -4(5) + 5 = -20 + 5 = -15 \] So, \( (q \circ r)(2) = -15 \). Putting it all together, we have: \[ (r \circ q)(2) = 0 \] \[ (q \circ r)(2) = -15 \]